Pitajte ljude - Izgradnja politika urbanog turizma od percepcije stanovnika - slučaj Novi Sad, Evropska prestonica kulture 2022 - Milenkovic, Nemanja; Vernot Maksić, Ana (Turizam, 2022)
Tourism destinations need to actively engage all their stakeholders that apart tourists, service providers, investors, etc., also includes residents that are not always in the focus of decision-makers. However, they can be a strong opponent when showing resentment towards the tourism development or the proposed plans. Therefore, the paper analyses the perception of residents towards the urban spaces of Novi Sad. The city is awarded as the European Capital of Culture for 2021 and therefore reassess its urban settings and tourism policies with respect to the wishes of residents. Data for the research was collected by in-person interviews with 797 local residents. The results show the residents are primarily satisfied with the green/recreational areas, and the most visited point is the city center. The essential urban markers are Petrovaradin Fortress, The Name of Mary Church, The Matica srpska, The Danube, and Serbian National Theatre. From the practical perspective, the results can enable authorities and tourism officials to identify spatially dependent attributes that are important for the destination image and residents’ quality of life.